Trunk melanoma - Mate, Miguel; Priario, Julio C (Cirugía del Uruguay, 1974)
The forms and extension of lesions of the malignant tumors of the trunk. An analysis was made of the lymphoganglionar regions which are more frequently attacked. Stress is placed on how particularly serious tumors in these regions ca be, and the special therapeutic recommendations for these cases are given in detail.